New Approach for Preparing Solid Lipid Nanoparticles with Volatile Oil-Loaded Quercetin Using the Phase-Inversion Temperature Method - Yotsanan Weerapol; Suwisit Manmuan; Nattaya Chaothanaphat; Sontaya Limmatvapirat; Jitnapa Sirirak; Poomipat Tamdee; Sukannika Tubtimsri (MDPI AG, 2022)
Quercetin (QCT), a natural flavonoid, is of research interest owing to its pharmacological properties. However, its pharmacokinetic limitations could hinder its widespread therapeutic use. Nanocarriers, especially solid lipid nanoparticles (SLNs), might overcome this constraint. This study aimed to investigate QCT-loaded SLNs prepared via a new approach using a volatile oil. The phase-inversion temperature method was used to incorporate rosemary oil (RMO) into SLNs prepared using solid lipids possessing different chemical structures. Among the solid lipids used in the formulations, trilaurin (TLR) exhibited the smallest particle size and good stability after a temperature cycling test. SLNs prepared with a ratio of RMO to TLR of 1:3 could load QCT with an entrapment efficiency of >60% and drug loading of ~2% w/w. The smallest particle size was achieved using the polyoxyethylene-hydrogenated castor oil RH40, and the particle size depended on the concentration. The drug-release profile of QCT_TLR exhibited prolonged biphasic release for >24 h. QCT_TLR was a safe formulation, as indicated by a cell viability percentage of >75% at <2% v/v. In a computer simulation, the system with RMO enabled smaller sized SLNs than those without RMO. This new discovery shows great promise for producing SLNs via the phase-inversion temperature method with incorporation of volatile oil, particularly for delivering compounds with limited water solubility.